2019
DOI: 10.1007/s10113-019-01480-0
|View full text |Cite
|
Sign up to set email alerts
|

Consequences for bird diversity from a decrease in a foundation species—replacing Scots pine stands with Norway spruce in southern Sweden

Abstract: Forest ecosystems are often defined by their dominant foundation tree species, which dictate forest structure and ecosystem processes. In southern Sweden, concerns are being raised because production stands of a foundation tree species, Scots pine (Pinus sylvestris), are being converted to Norway spruce (Picea abies) stands. Such conversions may lead to biodiversity loss, though the specific nature and extent of such losses remain unknown. Here, we assess the potential biodiversity impacts by contrasting the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Goldcrest (Regulus regulus) may also contribute to differences in community composition, as this species is often associated with spruce (Haapanen 1965). Targeted surveys of 55 and 80-year-old spruce and pine production stands in southern Sweden found that bird community composition differed in line with these expectations, but that older spruce stands can support higher bird diversity than pine, with effects depending on rotation length and broadleaf retention practices (Lindbladh et al 2019).…”
Section: Bird Communitiesmentioning
confidence: 83%
“…Goldcrest (Regulus regulus) may also contribute to differences in community composition, as this species is often associated with spruce (Haapanen 1965). Targeted surveys of 55 and 80-year-old spruce and pine production stands in southern Sweden found that bird community composition differed in line with these expectations, but that older spruce stands can support higher bird diversity than pine, with effects depending on rotation length and broadleaf retention practices (Lindbladh et al 2019).…”
Section: Bird Communitiesmentioning
confidence: 83%
“…2). This may reflect the fact that several of the reserves included in this study lacked some old‐growth forest characteristics (see Lindbladh et al ., 2019). However, the outcome may also reflect the difficulties involved in finding bird species indicative of high natural values in this region.…”
Section: Discussionmentioning
confidence: 99%
“…We used survey data from three published (Lindbladh et al, 2014b(Lindbladh et al, , 2017(Lindbladh et al, , 2019 and one unpublished study (A. Felton, P.-O. Hedwall, E. Holmstr€ om, R. Trubins, J. Lagerstedt, & M. Lindbladh, in prep).…”
Section: Study Area and Stands Includedmentioning
confidence: 99%
See 2 more Smart Citations